Revision of the Lower Ordovician (lower Floian; Tulean) pliomerid trilobite Protopliomerella, with new species from the Great Basin, western USA - Mcadams, Neo E. B.; Adrain, Jonathan M. (Zootaxa, 2011)
New field sampling of classic Ibexian sections in the Great Basin has resulted in the discovery of several new species assignable to the pliomerid trilobite genus Protopliomerella Harrington, 1957. The genus was originally monotypic and based on Protopliomerops contracta Ross, 1951. Protopliomerella pauca Demeter, 1973, was later added, but it is shown herein to be a junior subjective synonym of P. contracta. The material originally assigned to Protopliomerella contracta by Ross belongs to as many as three distinct, stratigraphically separate species. New species include P. stegneri, P. bowlesi, P. kerouaci, P. seegeri, and P. okeeffeae. Two additional new species are not well enough known to name and are reported in open nomenclature. The phylogenetic status of Protopliomerella, as thus conceived, is ambiguous and the taxon may be rendered paraphyletic by the genera Pseudocybele Ross, 1951, and Lemureops McAdams and Adrain, 2009.